TEKNOLOGI MEDIA PEMBELAJARAN BAHASA ARAB - Sholihah, Euis; Supardi, Adi; Hilmi, Irpan (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2022)
This study aims to examine the technology used by SD Ar-Rafi' Bandung in Arabic learning media. The development of a modern nation is characterized by technological developments. Because today's technology has become public consumption and has entered into many areas of life, one of which is in the realm of education. Arabic language education is also characterized by increased interest and high motivation, when supported by the provision of relevant media. This study uses a qualitative type with literature that explores information with Arabic learning media that can be used by teachers. The result is that there are three kinds of Arabic learning media that can be developed, namely audio, visual, and audio-visual media. Radio, CD, MP3, and podcasts are examples of audio media. While pictures, posters, flash cards, and power point slides are visual forms. The audio-visual media for example video, film, or the internet. Teachers can take advantage of internet technology that can be accessed easily, for example by using YouTube channels, social media, or online Arabic learning sites. There is no doubt that the right learning media plays an important role in creating and providing a pleasant learning experience. In today's modern era, teachers can develop various learning media by utilizing available learning media, both in digital and analog form. The selection of instructional media depends on several aspects, taking into account the accuracy of the learning objectives and student conditions.